Penurunan Perilaku Merokok Sebagai Pengendali Tekanan Darah Bagi Masyarakat - Sawitri, Endang; marwanti, marwanti; supardi, supardi; Purnomo, Romadhani Tri; Mawardi , Mawardi; Febriati, Desi (Universitas Muhammadiyah Klaten, 2024)
The habit of smoking is very detrimental to health, as it can trigger various diseases such as cancer, heart attack, impotence, pregnancy and fetal disorders. If the smoking habit continues for a long period of time it can cause death. To analyze the relationship between smoking habits and blood pressure. This type of research is Analytical observational with Cross Sectional design, data collection is done by visiting the respondent's house one by one. 88 men were willing to be respondentsRespondents who had mild smoking behavior with normal blood pressure were 5 respondents, respondents who had mild smoking behavior with prehypertension blood pressure were 5 respondents, respondents who had moderate smoking behavior with normal blood pressure were 28 respondents, respondents who had moderate smoking behavior with prehypertension blood pressure were 24 respondents, respondents who had moderate smoking behavior with Stage 1 hypertension blood pressure were 5 respondents, respondents who had heavy smoking behavior with normal blood pressure were 13 respondents, respondents who had heavy smoking behavior with prehypertension blood pressure were 8 respondents. Based on the results of the bevariate analysis, there is an insignificant relationship between smoking habits and blood pressure in RW 01 Juwiran Village, Juwiring District, Klaten Regency, which is indicated by a coefficient value of -0.094 with a p value of 0.386 (P>0.05).